2002
DOI: 10.1021/ja027885u
|View full text |Cite
|
Sign up to set email alerts
|

DNA Detection and Signal Amplification via an Engineered Allosteric Enzyme

Abstract: Rapid, sensitive, and sequence-specific DNA detection can be achieved in one step using an engineered intrasterically regulated enzyme. The semi-synthetic inhibitor-DNA-enzyme (IDE) construct (left) rests in the inactive state, but upon exposure to a complementary DNA sequence undergoes a DNA hybridization-triggered allosteric enzyme activation (right). The ensuing rapid substrate turnover provides the built-in signal amplification mechanism for detecting approximately 10 femtomoles of DNA in less than three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
155
0
5

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(160 citation statements)
references
References 19 publications
0
155
0
5
Order By: Relevance
“…[3][4][5] All proteins are mechanosensitive since they are elastic-these properties are at the heart of molecular dynamic computations. [6][7][8] Numerous studies have also indicated that mechanical forces can regulate gene expression. [9][10][11][12] There are feedback loops incorporating cancer malignancy and metastasis, 17,18 blood vessel angiogenesis, [19][20][21][22] bone growth and osteoporosis and lung, heart and skeleton muscle metabolism.…”
Section: Mechanical Force and Biologymentioning
confidence: 99%
“…[3][4][5] All proteins are mechanosensitive since they are elastic-these properties are at the heart of molecular dynamic computations. [6][7][8] Numerous studies have also indicated that mechanical forces can regulate gene expression. [9][10][11][12] There are feedback loops incorporating cancer malignancy and metastasis, 17,18 blood vessel angiogenesis, [19][20][21][22] bone growth and osteoporosis and lung, heart and skeleton muscle metabolism.…”
Section: Mechanical Force and Biologymentioning
confidence: 99%
“…Examples of such structures include autonomous walkers 15,16 , nanotweezers [17][18][19][20] and nanocages for controlled encapsulation and payload release 21,22 . New protein-DNA conjugation chemistries make it possible to precisely position proteins and other biomolecules on DNA scaffolds 23 , generating multi-enzyme pathways with the ability to modulate intermolecular interactions and the local environment [24][25][26][27][28][29][30] .…”
mentioning
confidence: 99%
“…[15] The proposed mechanism resembles the opening of molecular beacons, [16] or beacon-like enzyme-oligonucleotide-tethered inhibitors. [17] This oligomerization effect is also observed when shorter oligonucleotide complements are utilized (Figure 2). However, the oligomeric species produced over the time course of the experiment are smaller with respect to mass.…”
mentioning
confidence: 73%